Efeito antioxidante da creatina não protege da suscetibilidade à convulsões após traumatismo crânioencefálico em ratos - Saraiva, André Luis Lopes (2011)
Studies over recent years have highlighted the important role of creatine in health and in treating various neurological diseases. However, its role in secondary damage induced by traumatic brain injury (TBI) is not fully understood. The aim of this study was to evaluate the effect of creatine supplementation on the oxidative damage and susceptibility to seizures after TBI. For this, we used the model of fluid percussion injury (FPI) in rats, where brain damage is caused by a liquid column that causes a pressure on the dura intact of animal, which was previously exposed. Our results revealed that at 4 and 8 days after TBI, there was increased oxidative damage characterized by increased protein carbonylation and levels of species thiobarbituric acid reactive substances (TBARS), and also there was a reduction in Na+, K+ -ATPase activity. Statistical analysis (two way ANOVA) also revealed that creatine supplementation (300 mg / kg orally), beginning 30 minutes after TBI and continuing until 3, or 7 days after injury, reduced protein carbonylation and TBARS when analyzed at 4 and 8 days after injury. However, creatine supplementation did not protect the inhibition of Na+, K+-ATPase 4 and 8 days after TBI. Furthermore, the analysis electroencephalographic (EEG) showed that injection of a subconvulsant dose (35 mg / kg, intraperitoneally) of pentylenetetrazol (PTZ), 4 but not 8 days after TBI, decreased latency to the tonic- clonic seizures and increased the time spend in generalized seizure, when compared to the control group. Creatine supplementation had no effect on the convulsive parameters induced by PTZ injection. The experiments in this study suggest that in this experimental model of TBI, oxidative damage seems not to be directly involved in susceptibility to seizures after neuronal injury since the antioxidant capacity exerted by creatine does not protect against PTZ-induced seizures after TBI